Preservation, Digital Technology & Culture (PDT&C) (De Gruyter Saur, 2013)
Preservation, Digital Technology & Culture (PDT&C) is an international journal which focuses on preserving digital content from a wide variety of perspectives, including technological, social, economic, political, and user. Its scope is global, covering projects and practices from key international players in the field. The goal of the journal is to provide a timely forum for refereed articles, news, and field notes from around the world.